Theoretical investigations into the charge transfer properties of thiophene α-substituted naphthodithiophene diimides: excellent n-channel and ambipolar organic semiconductors. Issue 21 (18th May 2017) - Ji, Li-Fei; Fan, Jian-Xun; Zhang, Shou-Feng; Ren, Ai-Min
Abstract : The effects of substituents at the thiophene α-position ofNDTI on the electronic structures, stability, molecular packing and the charge transport properties were investigated using quantum chemical methods. Abstract : A theoretical study was carried out to investigate the electronic structures and the charge transport properties of a series of naphthodithiophene diimide (NDTI ) thiophene α-substituted derivativesNDTI-X using density functional theory and classical Marcus charge transfer theory. This study deeply revealed the structure–property relationships by analyzing the intermolecular interactions in crystal structures ofC8-NDTI andC8-NDTI-Cl thoroughly by using the Hirshfeld surface, QTAIM theories and symmetry-adapted perturbation theory (SAPT). Our results suggested that a 2-D brick-like π-stacking structure makesC8-NDTI-Cl a more excellent n-type semiconducting material with μ max-e of 2.554 cm 2 V −1 s −1 thanC8-NDTI with a herringbone-like slipped π-stacking motif. In addition, the calculated results showed that by modifying the thiophene α-positions ofNDTI with electron-withdrawing substituents, –F, –Cl and –CN, low-lying LUMO energy levels and a high adiabatic electron affinity EA(a) can be obtained; while introducing electron-donating groups, benzene (–B), thiophene (–T), benzo[ b ]thiophene (–BT) and naphtha[2, 3- b ]thiophene (–NT), expanded the molecular π-conjugated backbone, and narrow band gaps, high EA(a) and small reorganization energies can be obtained. Theoretical simulations predict thatNDTI-CN is an excellent air-stable n-type organic semiconducting material with an average electron mobility μ e of up to 1.743 cm 2 V −1 s −1 . Owing to their high EA(a), moderate adiabatic ionization potential IP(a) as well as small hole and electron reorganization energies, NDTI-BT andNDTI-NT are two well-balanced air-stable ambipolar semiconducting materials. The theoretical average hole/electron mobilities are as high as 2.708/3.739 cm 2 V −1 s −1 forC8-NDTI-NT and 1.597/2.350 cm 2 V −1 s −1 forC8-NDTI-BT, respectively.